Study on molecular mechanism of ANOS1 promoting development of colorectal cancer. - Lu Qi; Wenjuan Zhang; Zhiqiang Cheng; Na Tang; Yanqing Ding (PLoS ONE, 2017)
Our main aim was to elucidate the molecular mechanism responsible for the development and metastasis of colorectal cancer. Furthermore, we also identified the key genes participating in this molecular mechanism and stimulating the progression of colorectal cancer. In our experiment, the ANOS1 gene showed up-regulated expression levels continuously, whereas the methylation level showed downregulated levels when the colorectal cancer progressed through the four clinical stages of development and metastasis. We obtained this information by analyzing the expression profile data and methylation data of ANOS1 gene in colorectal cancer. This phenomenon indicates that ANOS1 gene shows continuous activation during the progression of colorectal cancer. According to the results of survival analysis, the expression of ANOS1 gene is closely related to the overall survival rate of patients (p = 0.003); moreover, the expression of ANOS1 gene is also strongly associated with the disease-specific survival rate (p = 0.001). When the expression of ANOS1 gene is high, the survival rate is low in patients. When the expression of ANOS1 gene is low, the survival rate of patients is high. To elucidate the possible molecular mechanism of ANOS1, we performed GSEA enrichment analysis based on the expression value of ANOS1 gene. We found that gene with an up-regulated expression was mainly involved in Wnt signaling pathway; these up-regulated genes were present in the group of high ANOS1 expression. Although several genes were involved in Wnt signaling pathway, CTHRC1 gene was of higher occurrence frequency. By co-expression analysis, we found that both expression value and expression extent of CTHRC1 were associated with ANOS1. All these results indicate that ANOS1 possibly promotes the activation of Wnt signaling pathway with its co-expression partner CTHRC1. Thus, ANOS1 and CTHRC1 genes promote the development and metastasis of colorectal cancer.